The genetic and molecular features of the intronic pentanucleotide repeat expansion in spinocerebellar ataxia type 10 - Kurosaki, Tatsuaki; Ashizawa, Tetsuo (Frontiers in Genetics, 2022)
Spinocerebellar ataxia type 10 (SCA10) is characterized by progressive cerebellar neurodegeneration and, in many patients, epilepsy. This disease mainly occurs in individuals with Indigenous American or East Asian ancestry, with strong evidence supporting a founder effect. The mutation causing SCA10 is a large expansion in an ATTCT pentanucleotide repeat in intron 9 of the ATXN10 gene. The ATTCT repeat is highly unstable, expanding to 280-4,500 repeats in affected patients compared with the 9-32 repeats in normal individuals, one of the largest repeat expansions causing neurological disorders identified to date. However, the underlying molecular basis of how this huge repeat expansion evolves and contributes to the SCA10 phenotype remains largely unknown. Recent progress in next-generation DNA sequencing technologies has established that the SCA10 repeat sequence has a highly heterogeneous structure. Here we summarize what is known about the structure and origin of SCA10 repeats, discuss the potential contribution of variant repeats to the SCA10 disease phenotype, and explore how this information can be exploited for therapeutic benefit.